Isolation and culture of primary human pancreatic stellate cells that reflect the context of their tissue of origin - Strobel, Oliver; Dadabaeva, Nigora; Felix, Klaus M.; Hackert, Thilo; Giese, Nathalia; Jesenofsky, Ralf; Werner, Jens (Langenbeck's archives of surgery, 2016)
Background: Pancreatic stellate cells (PSCs) play a critical role in pancreatic ductal adenocarcinoma (PDAC). Activated PSCs are the main source of fibrosis in chronic pancreatitis and of desmoplasia in PDAC. The majority of studies on PSC are based on in vitro experiments relying on immortalized cell lines derived from diseased human pancreas or from animal models. These PSCs are usually activated and may not represent the biological context of their tissue of origin. Purpose: (1) To isolate and culture primary human PSC from different disease contexts with minimal impact on their state of activation. (2) To perform a comparative analysis of phenotypes of PSC derived from different contexts.MethodsPSCs were isolated from normal pancreas, chronic pancreatitis, and PDAC using a hybrid method of digestion and outgrowth. To minimize activation by serum compounds, cells were cultured in a low-serum environment (2.5 % fetal bovine serum (FBS)). Expression patterns of commonly used markers for PSC phenotype and activity were compared between primary PSC lines derived from different contexts and correlated to expression in their original tissues. Results: Isolation was successful from 14 of 17 tissues (82 %). Isolated PSC displayed stable viability and phenotype in low-serum environment. Expression profiles of isolated PSC and matched original tissues were closely correlated. PDAC-derived PSC tended to have a higher status of activation if compared to PSC derived from non-cancerous tissues. Conclusions: Primary human PSCs isolated from different contexts and cultured in a low-serum environment maintain a phenotype that reflects the stromal activity present in their tissue of origin.
Gesehen am 08.02.2019
Published online: 29 December 2015